Implementasi Merdeka Belajar Dalam Pembelajaran Pendidikan Agama Islam Pada Pendidikan Dasar - Wahidah, Evita Yuliatul; Sulaeman, Radzie (STAI Al-Musaddadiyah Garut, 2024)
The evolution of education in Indonesia is closely tied to curriculum reforms, which undergo evaluations at specific intervals. There is a common perception that curriculum changes occur with shifts in policy leadership. Currently, the new curriculum introduced is the